Determining Consumer Intention: Uncovering the Influential Factors in Customer Switching from LPG to Induction Stoves in Indonesia - Citra Putri Sakinna; Tengku Ezni Balqiah (Eduvest - Journal of Universal Studies, 2024)
The increasing electrification of lifestyles in Indonesia has prompted a shift in consumer preferences, particularly regarding kitchen appliances. Indonesia is currently facing an electricity oversupply issue, hence migrating consumers from traditional Liquified Petroleum Gas (LPG) stoves to induction stoves offers the potential to enhance electricity utilization and effectively address this predicament. This study aims to investigate the influential factors behind consumers' intentions to switch from traditional LPG stoves to induction stoves. The data were collected from 802 traditional LPG stoves consumers, who are Indonesian citizens, residing across various regions of Indonesia, and have not previously purchased an induction stove to achieve the objective. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal the importance of Push, Pull, and Mooring factors in motivating consumers to switch from LPG stoves to induction stoves. This research contributes critical insights to academia, industry, and policymakers as well, offering a nuanced understanding of the dynamics influencing this transition in the Indonesian market and playing a pivotal role in addressing the electricity oversupply issue in Indonesia.